Comparison of twitch contractile properties of plantarflexor muscles in Nordic combined athletes, cross-country skiers, and sedentary men - Ereline, J.; Gapeyeva, H.; Paumlaumlsuke, M. (European Journal of Sport Science, 2011)
The purpose of this study was to compare twitch contractile properties of skeletal muscles in male athletes who train for power and endurance simultaneously (Nordic combined athletes) with athletes who train for endurance (cross-country skiers) and sedentary individuals. Ten Nordic combined athletes, 13 cross-country skiers, and 14 sedentary males aged 20-26 years participated. To determine the contractile properties of the plantarflexor muscles during isometric twitch, the posterior tibial nerve in the popliteal fossa was stimulated by supramaximal square wave pulses of 1 ms duration. Twitch peak force, maximal rates of force development and relaxation, contraction and half-relaxation times were measured. The percentage increase in twitch peak force after a 5-s maximal voluntary contraction (MVC) was taken as an indicator of post-activation potentiation. Nordic combined athletes had a significantly greater twitch post-activation potentiation and rate of force development and shorter contraction time than the other two groups (P < 0.05). They also had a greater (P < 0.05) twitch peak force than cross-country skiers. No significant differences in measured twitch contraction characteristics were found in cross-country skiers and sedentary males. We conclude that the twitch contractile properties of the plantarflexor muscles differed markedly in athletes who train for power and endurance simultaneously compared with athletes who predominantly train for endurance. As an indicator of long-term adaptation to simultaneous power and endurance training, increased twitch force-generation and potentiation capacity, and shortening of twitch contraction times in the plantarflexor muscles were observed in Nordic combined athletes.